2007
DOI: 10.1124/mol.107.036574
|View full text |Cite
|
Sign up to set email alerts
|

A New Steroid Derivative Stabilizes G-Quadruplexes and Induces Telomere Uncapping in Human Tumor Cells

Abstract: Human telomeric DNA consists of tandem repeats of the sequence d(TTAGGG) with a 3Ј single-stranded extension (the G-overhang). The stabilization of G-quadruplexes in the human telomeric sequence by small-molecule ligands inhibits the activity of telomerase and results in telomere uncapping, leading to senescence or apoptosis of tumor cells. Therefore, the search for new and selective G-quadruplex ligands is of considerable interest because a selective ligand might provide a telomere-targeted therapeutic approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 71 publications
5
56
0
Order By: Relevance
“…A preferred role of the guanidinium group in quadruplex ligands is supported by two independent dynamic combinatorial libraries targeting quadruplex DNA, which both identified the guanidinium-containing compounds as the favored library members, 43,44 and by the higher efficiency of the guanidinium-containing steroid FG exhibited compared to the analogous trimethylammonium steroid maouetine. 45 …”
Section: Resultsmentioning
confidence: 97%
“…A preferred role of the guanidinium group in quadruplex ligands is supported by two independent dynamic combinatorial libraries targeting quadruplex DNA, which both identified the guanidinium-containing compounds as the favored library members, 43,44 and by the higher efficiency of the guanidinium-containing steroid FG exhibited compared to the analogous trimethylammonium steroid maouetine. 45 …”
Section: Resultsmentioning
confidence: 97%
“…[59] Recently, some G-quadruplex ligands have been found to interfere with the conformation and length of the telomeric G-overhang; [60] other studies have also shown that some G-quadruplex ligands may function by dissociation of the telomere binding proteins POT1 (protection of telomeres 1) and TRF2 (telomeric repeat binding factor 2) and uncapping telomeres to make them available for extension. [61][62][63][64] Additionally, the biological functions of telomeres are likely to be dependent on the nature of their various structural states. For example, hybrid quadruplexes can occur within a 3'-end overhang, and the subsequent packaging enables the formation of a so-called t-loop at the end of the chromosome, which is likely to provide flexibility for responding to such environmental changes as protein binding.…”
Section: Telomeresmentioning
confidence: 99%
“…Telomere capping alterations have been associated with G-quadruplex formation. Brassart et al screened natural and synthetic derivatives and identified two natural compounds as potent inducers of G-quadruplex configuration [119]. Both, malouetine (34) isolated from leaves of Malouetia bequaaertiana E. Woodson and a funtumine derivative called funtumine guanylhydrazone (35) from the leaves of Funtuna latifolia stapf induced G-quadruplex stabilization.…”
Section: Telomerase Inhibitorsmentioning
confidence: 98%